Campaigns and conflict on social media: a literature snapshot. Issue 5 (12th September 2016) - Boulianne, Shelley
Abstract : Purpose: The purpose of this paper is to discuss the themes identified in the submissions to this volume. The findings are contextualized in recent scholarship on these themes. Design/methodology/approach: The discussion is organized around predicting social media use among candidates, organizations, and citizens, then exploring differences in the content of social media postings among candidates, organizations, and citizens, and finally exploring the impact of social media use on mobilization and participatory inequality defined by gender, age, and socio-economic status. Findings: This volume addresses whether social media use is more common among liberal or conservative citizens, candidates, and organizations; the level of negativity in social media discourse and the impact on attitudes; the existence of echo chambers of like-minded individuals and groups; the extent and nature of interactivity in social media; and whether social media will reinforce participation inequalities. In sum, the studies suggest that negativity and interactivity on social media are limited and mixed support for echo chambers. While social media mobilizes citizens, these citizens are those who already pre-disposed to engage in civic and political life. Originality/value: This paper explores key topics in social media research drawing upon 60 recently published studies. Most of the studies are published in 2015 and 2016, providing a contemporary analysis of these topics.